Predicting Purchase Intention Based on Salesperson Behavior, Social Utility, Psychological Utility, and Economic Utility - Derakhshan, Fatemeh Sadat; Mahdad, Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: The objective of this study was to predict consumers’ purchase intention based on salesperson behavior, economic utility, social utility, and psychological utility.Methods and Materials: This applied study employed a descriptive–correlational design and was conducted using a cross-sectional survey method. The statistical population consisted of consumers who completed online questionnaires during May and June 2025. A total of 377 valid questionnaires were analyzed after excluding incomplete responses. Data collection instruments included researcher-developed questionnaires measuring purchase intention, salesperson behavior, economic utility, social utility, and psychological utility, all assessed on five-point Likert scales. Content validity was confirmed by subject-matter experts, and reliability was evaluated using Cronbach’s alpha. Data analysis was carried out using SPSS version 26, applying Pearson correlation analysis and stepwise multiple regression to examine the predictive relationships among variables.Findings: Inferential analyses indicated that purchase intention was positively and significantly correlated with salesperson behavior, economic utility, social utility, and psychological utility (p ≤ .01). Stepwise multiple regression analysis showed that economic utility entered the regression model in the first step and explained 24% of the variance in purchase intention (p = .001). In the second step, social utility entered the model and, together with economic utility, explained 27% of the variance in purchase intention (p = .001). Psychological utility and salesperson behavior did not retain significant predictive power in the final regression model.Conclusion: The findings demonstrate that consumers’ purchase intention is primarily driven by economic utility and, to a lesser extent, social utility, highlighting the dominant role of cost–benefit evaluations and social value considerations in purchase decision-making. These results suggest that while psychological benefits and salesperson behavior are important correlates, their influence on purchase intention may be indirect and mediated through perceived value dimensions.